Jenis dan Model Evaluasi Pendidikan di Lingkungan Pesantren - Fahmi Hasbi Arrosyad; M. Fuad Hasan (Almustofa Journal of Islamic Studies and Research, 2025)
Islamic  boarding  schools  (pesantren)  are  the  oldest  Islamic  educational institutions in Indonesia, facing major challenges in balancing tradition with the demands  of  modernity.  The  typological  diversity  of  pesantren—ranging  from purely  Salafiyah,  modern  (Khalafiyah),  to  integrated  pesantren—creates variations in curriculum management and evaluation systems. This study aims to analyze  the  types  and  models  of  educational  evaluation  in  pesantren  through  a qualitative  literature  review  approach.  The  findings  reveal  that  Salafiyahpesantren  emphasize  authentic  and  qualitative  evaluation  based  on  mastery  of classical  Islamic  texts  (kitab  kuning)  and  students’  moral  development,  while modern  pesantren  adopt  formal  evaluations  in  accordance  with  government standards. Integrated pesantren, meanwhile, apply a dual evaluation system that balances  formal  academic  achievement  with  the  depth  of  religious  knowledge. These findings highlight that integrating traditional and formal evaluation models is crucial to ensuring educational accountability while preserving the authenticity of pesantren.